Rhododendron x 'George Tabor' 'George Tabor' Azalea: FPS509/FP509, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Rhododendron x ‘George Taber’ azalea, a large, spreading evergreen azalea known for its impressive appearance in mass plantings and as a specimen planting. It highlights the plant’s characteristics, including its suitability for various landscaping uses. Additionally, the document mentions related azalea varieties and provides links to further resources on azalea pest management and other horticultural topics. The information is part of the University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS) Extension outreach. Original publication date October 1999.